2008
DOI: 10.1007/s10295-008-0477-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of extracellular esterase and lipase activities from five halophilic archaeal strains

Abstract: A total of 118 halophilic archaeal collection of strains were screened for lipolytic activity and 18 of them were found positive on Rhodamine agar plates. The selected five isolates were further characterized to determine their optimum esterase and lipase activities at various ranges of salt, temperature and pH. The esterase and lipase activities were determined by the hydrolysis of pNPB and pNPP, respectively. The maximum hydrolytic activities were found in the supernatants of the isolates grown at complex me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 29 publications
2
36
2
3
Order By: Relevance
“…In our study, the lipase activity has continuously increased during the incubation period and the maximum activity (4.73 U/ml) was recorded at the 56th day in 4 M NaCl. The lipase activity of the cultures containing 3 M and 5 M NaCl were recorded as 3.85 U/ml and 4.34 U/ml, respectively which are higher than the results reported by Ozcan et al (2009) 18 . Salt concentrations above 4M was determined not to have a signifi cant effect on the lipase production, furthermore has an adverse effect on the lipolytic activity and cell growth.…”
Section: 21contrasting
confidence: 74%
“…In our study, the lipase activity has continuously increased during the incubation period and the maximum activity (4.73 U/ml) was recorded at the 56th day in 4 M NaCl. The lipase activity of the cultures containing 3 M and 5 M NaCl were recorded as 3.85 U/ml and 4.34 U/ml, respectively which are higher than the results reported by Ozcan et al (2009) 18 . Salt concentrations above 4M was determined not to have a signifi cant effect on the lipase production, furthermore has an adverse effect on the lipolytic activity and cell growth.…”
Section: 21contrasting
confidence: 74%
“…The archaeal enzyme reported as the most thermostable and thermoactive esterase known to date (Ikeda and Clark 1998). In our laboratory, the halophilic archaeal isolates, grown best in a range of 2-5 M NaCl, produced high lipolytic activity in the range of 3-4.5 M NaCl (Ozcan et al, 2009). It was found that the lipolytic activity dropped at 5 M NaCl.…”
Section: Biotechnological Importance Of Archaeamentioning
confidence: 76%
“…The sources for these biocatalysts have been animals, plants, fungi and mostly bacteria. Recently, the extremophilic bacteria and archaea have become more popular since the enzymes of these organisms are able to remain catalytically active under extremes of temperature, salinity, pH and pressure (Synowiecki et al, 2006;Ozcan et al, 2009). In biotechnology for an efficient application, one has to determine the most suitable enzymes and best reaction conditions.…”
Section: Biotechnological Importance Of Archaeamentioning
confidence: 99%
See 1 more Smart Citation
“…After that, a total of 118 halophilic archaeal strains were screened for lipolytic activity. Five isolates were selected and further characterized, indicating the presence of salt-dependent and temperature-tolerant lipolytic enzymes [72]. Camacho et al studied the production of esterase and lipase in Haloarcula marismortui [73]: they observed high production rates of intracellular esterase and lipase using p-nitrophenyl valerate and p-nitrophenyl laurate, respectively.…”
Section: Esterases and Lipasesmentioning
confidence: 99%